Photo‐Driven Hydrogen Evolution by an Artificial Hydrogenase Utilizing the Biotin‐Streptavidin Technology. Issue 4 (16th April 2018) - Keller, Sascha G.; Probst, Benjamin; Heinisch, Tillmann; Alberto, Roger; Ward, Thomas R.
Abstract : Photocatalytic hydrogen evolution by an artificial hydrogenase based on the biotin‐streptavidin technology is reported. A biotinylated cobalt pentapyridyl‐based hydrogen evolution catalyst (HEC) was incorporated into different mutants of streptavidin. Catalysis with [Ru(bpy)3 ]Cl2 as a photosensitizer (PS) and ascorbate as sacrificial electron donor (SED) at different pH values highlighted the impact of close lying amino acids that may act as a proton relay under the reaction conditions (Asp, Arg, Lys). In the presence of a close‐lying lysine residue, both, the rates were improved, and the reaction was initiated much faster. The X‐ray crystal structure of the artificial hydrogenase reveals a distance of 8.8 Å between the closest lying Co‐moieties. We thus suggest that the hydrogen evolution mechanism proceeds via a single Co centre. Our findings highlight that streptavidin is a versatile host protein for the assembly of artificial hydrogenases and their activity can be fine‐tuned via mutagenesis. Abstract :